2013
DOI: 10.1063/1.4829508
|View full text |Cite
|
Sign up to set email alerts
|

Six-dimensional quantum dynamics study for the dissociative adsorption of HCl on Au(111) surface

Abstract: The six-dimensional quantum dynamics calculations for the dissociative chemisorption of HCl on Au(111) are carried out using the time-dependent wave-packet approach, based on an accurate PES which was recently developed by neural network fitting to density functional theory energy points. The influence of vibrational excitation and rotational orientation of HCl on the reactivity is investigated by calculating the exact six-dimensional dissociation probabilities, as well as the four-dimensional fixed-site disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 62 publications
12
66
0
Order By: Relevance
“…33 A new finding for the site-averaging approximation was presented for both reactions for HCl/DCl initially in (v = 0, j = 0) state, 31,32 i.e., the 6D dissociation probability can essentially be reproduced without ZPE corrections by averaging the 4D site-specific dissociation probabilities over impact sites, as long as enough impact points are used in the averaging. If the validity of this new site-averaging approximation generally holds in other molecule-surface reactions, it should be a very promising approach to investigate the moleculesurface reactions at a full-dimensional quantum mechanical level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 A new finding for the site-averaging approximation was presented for both reactions for HCl/DCl initially in (v = 0, j = 0) state, 31,32 i.e., the 6D dissociation probability can essentially be reproduced without ZPE corrections by averaging the 4D site-specific dissociation probabilities over impact sites, as long as enough impact points are used in the averaging. If the validity of this new site-averaging approximation generally holds in other molecule-surface reactions, it should be a very promising approach to investigate the moleculesurface reactions at a full-dimensional quantum mechanical level.…”
Section: Introductionmentioning
confidence: 99%
“…Such full-dimensional quantum dynamics calculations were limited to the diatomic molecules such as H 2 dissociating on metal surfaces, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and the recent work of HCl/DCl dissociating on Au(111) surface. [31][32][33] Early in 1995, Gross et al carried out the first full-dimensional quantum dynamics calculation on non-activated dissociation of H 2 on Pd(100) surface. 25, 26 Kroes and co-workers demonstrated that electron-hole pair excitation need not be considered to obtain accurate results for activated dissociation of H 2 on Pt(111) surface by performing full-dimensional quantum dynamics calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to H 2 on Cu(111), HCl can dissociate on Au(111) over a reaction barrier (at E i > 1 eV, 17 calculated barrier height: 0.65 eV 18,19 ) and the reaction is strongly enhanced by vibrational excitation, 17 reflecting a possible late transition state. 18,20,21 Vibrational…”
Section: Introductionmentioning
confidence: 99%
“…In the studies presented in this review, there is no conclusive evidence that nonadiabatic effects influence the dissociation dynamics. Recent experiments on the dissociation of HCl on Au (111) by Shirhatti et al (145) measured the sticking coefficient to be much lower than predicted theoretically (146). A possible reason might be that the calculations neglect nonadiabatic effects, which have been observed in surface scattering experiments for the same system (14)(15)(16).…”
Section: Discussionmentioning
confidence: 89%